2020
DOI: 10.3390/toxins12020085
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of a Novel Bacterium, Slackia sp. D-G6: Detoxifying Deoxynivalenol and Producing the Natural Estrogen Analogue, Equol

Abstract: Deoxynivalenol (DON) is a highly abundant mycotoxin that exerts many adverse effects on humans and animals. Much effort has been made to control DON in the past, and bio-transformation has emerged as the most promising method. However, useful and effective application of bacterial bio-transformation for the purpose of inhibiting DON remains urgently needed. The current study isolated a novel DON detoxifying bacterium, Slackia sp. D-G6 (D-G6), from chicken intestines. D-G6 is a Gram-positive, non-sporulating ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Contradictory findings have been reported in different studies about Slackia . For instance, a recent study reported that Slackia isolated from chicken intestine w as the best detoxifying agent against mycotoxin and helps improve chicken intestinal functions (Gao et al ., 2020 ). However, several other studies reported that Slackia was found to be significantly enriched in the microbiota of gastric carcinogenesis and not only caused disease progression but also gut dysbiosis (Coker et al ., 2018 ; Kharrat et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory findings have been reported in different studies about Slackia . For instance, a recent study reported that Slackia isolated from chicken intestine w as the best detoxifying agent against mycotoxin and helps improve chicken intestinal functions (Gao et al ., 2020 ). However, several other studies reported that Slackia was found to be significantly enriched in the microbiota of gastric carcinogenesis and not only caused disease progression but also gut dysbiosis (Coker et al ., 2018 ; Kharrat et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other DON-biotransformation products, including DON-glutathione conjugates and the products of glutathione degradation, such as DON-S-cysteinyl-glycine and DON-S-cysteine, have been reported in cereals. Thanks to intestinal microflora, DON could be metabolized in animals and humans but not deposited in the tissues [ 151 , 152 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
“…Nevertheless, the pure strain PGC-3-9 was chosen for its DON-degradation capabilities in media and wheat flour under both aerobic and anaerobic conditions ( Figure 5 and Figure 6 ). All pure strains exhibiting de-epoxidation activity on trichothecenes were anaerobic bacteria used as feed additives in animal intestinal and digestive systems [ 11 , 19 , 20 , 21 , 22 ]. Our results indicate that de-epoxidation of trichothecene mycotoxins can occur under both aerobic and anaerobic conditions.…”
Section: Discussionmentioning
confidence: 99%